2021
DOI: 10.1002/anbr.202100119
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Vocal Fold Regenerative Biomaterials: An Immunological Perspective

Abstract: The vocal folds are functional organs located in the larynx that play a critical role in our daily breathing, speech, and swallowing functions. A key structural feature of the vocal folds is their delicate mucosa, which consists of a thin, layered epithelium and underlying extracellular matrix (ECM)-rich lamina propria. [1,2] Irreversible changes to the vocal fold mucosa, such as scarring, atrophy, and sulcus vocalis, require regenerative technologies to stimulate a controlled regrowth of the tissue. An increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 210 publications
(228 reference statements)
0
13
0
Order By: Relevance
“…The induction of macrophage polarization toward the M2 phenotype would provide key evidence toward the applicability of VF dECM hydrogels toward VF repair. [8,77] Rather than solely relying on proteomic analyses and the presence of remnant immunogenic proteins, these results should be used in combination with in vivo studies to predict the immune response.…”
Section: Proteomic Insights Into Tissue Specificitymentioning
confidence: 99%
See 2 more Smart Citations
“…The induction of macrophage polarization toward the M2 phenotype would provide key evidence toward the applicability of VF dECM hydrogels toward VF repair. [8,77] Rather than solely relying on proteomic analyses and the presence of remnant immunogenic proteins, these results should be used in combination with in vivo studies to predict the immune response.…”
Section: Proteomic Insights Into Tissue Specificitymentioning
confidence: 99%
“…Mammalian vocal folds (VFs) have unique ECM‐structural and mucosa‐immunological profiles that likely benefit from a tissue‐specific regenerative approach like dECM. [ 8–10 ] Mass spectrometry has aided in profiling the proteome of organs of interest by measuring the mass‐to‐charge ratio (m z −1 ) of fragmented proteins in the sample. For complex ECM profiles like VF, proteomic analyses are imperative to generate a deep understanding of the interaction between biological systems and biomaterials for bioengineering applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMMA is used in cured solid form as bone cement, for treating bone fractures and osteomyelitis [3] and in the treatments of bone tumors [4]. PMMA microspheres suspended in gel form are used in injections to correct congenital and acquired deformities such as Scleroderma en coup de sabre [5], in vocal cord medialization [6], in tissue engineering for the manufacture of heart valves [7], for treating urinary and fecal incontinence and gastroesophageal reflux [8], for treating acne scars [9], and in subcutaneous and juxta-dermal collagen biostimulation obtaining satisfactory results, with low complication rates [10].…”
Section: Introductionmentioning
confidence: 99%
“…As seen in other scarring conditions, 10 treatment runs the risk of triggering recurrent fibrosis and initiating a vicious cycle of scar deposition. A range of novel therapies have been trialed that aim to break this cycle, 11 , 12 , 13 but most remain experimental and in instances where data is available involving human subjects, 14 , 15 randomized controlled trials are yet to be reported.…”
Section: Introductionmentioning
confidence: 99%